Mendeley Integration Of Word Processing Application For Job Training Report Optimalization At Smks Ekuin Pangeran Jayakarta - Rakhmat Purnomo; Tri Dharma Putra (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
The word processing application, Microsoft Word, will make it easier for students to work on the job training report quickly and effectively. A lot of knowledge that students can get when making reports with a scientific approach. SMKS EKUIN Pangeran Jayakarta Vocational High School students have a problem with this. The purpose of this community service program is to overcome these problems, namely that students still do not optimize word processing applications to make job training reports with a scientific approach. The solution we give by providing mentoring training is effective in optimizing the use of word processing applications that are integrated with the Mendeley Library Manager and the use of the Style, Caption, and Equation functions. Participants were also presented with how to add and develop knowledge and practice the 10 finger fast typing method. The implementation methods carried out are (1) Presentation, the material is explained briefly, concisely and clearly, (2) Demonstration, the material is demonstrated directly, participants see it, (3) Direct Practice, participants carry out and practice the material presented, (4) Mentoring, Participants are helped during practice. Problems encountered can be resolved immediately, and (5) Google Classroom, utilization of this Learning Management System to see the progress of learning, discussion, and unlimited time assistance. Participants can asked the mentor anytime if there are any questions. The results of this program, after training, the first is that participants will know and gain knowledge and skills. Second, if participants always practice these skills, they will definitely be able to operate word processing applications optimally, typing can be completed quickly, tasks such as making papers, proposals, and any reports, especially job training reports, can be prepared properly and using a scientific approach so that their knowledge will increase.